UJI EFEKTIFITAS APLIKASI PUPUK TEH KOMPOS KULIT PISANG UNTUK MENINGKATKAN KETERSEDIAAN DAN SERAPAN KALIUM SERTA PRODUKSI UMBI BAWANG MERAH PADA ALFISOL - Ardo Aprilio; Retno Suntari; S Syekhfani (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Banana peel contains 15% potassium and 12% phosphorus more than the flesh of the fruit, so it is potential to be used as organic fertilizer. Utilization of waste of banana peel can improve the availability of K, K uptake and production of onion plants in Alfisols. This study used a completely randomized design with 8 treatments and 3 replications. The treatments were combinations of banana peel compost tea and KCl. The results showed there were significant differences in any parameter. Best result for availability K was a combination of 100% compost tea and 50% KCl amount of 0.88 cmol kg-1. Onion bulbs could absorb K for 20.88 mg plant-1 on the treatment of 00%Â  compost tea and 50% KCl. The dry weight of bulb produced by the treatment of 100% compost tea banana peel and 50% KCl was 31.16 g plant-1. K availability and K uptake by bulbs had a very strong relationship